Investigating the Effect of Viscous Damper on Seismic Behavior of Steel Dual Frames with Divergent Bracing Affected by Near and Far Fields Earthquake to Fault - Hamid Reza Ashrafi; Mozafar Shokri Rad; Yahya Adineh Far; Peyman Beiranvand; Soroush Dadgar (Civil Engineering Journal, 2017)
Current study is sought to study the effect of linear and nonlinear liquid viscous dampers on steel frames having dual systems of bending frame and divergent bracing. These frames were first designed according to regulations of Iran’s 2800 standard and tenth chapter of national regulations of construction (planning and performing steel construction) through equivalent static method then frames were modelled again in non-linear analysis software and time history non-linear analyses were done on them with installing viscous dampers on these frames using recorded near and far faults. In this study the effect of viscous dampers will be investigated on seismic behaviour of mentioned frames and results will be proposed in form of maximum graphs of relative displacements, stories lateral displacements, base shear maximum, waste energy graphs and dampers’ force-displacements. All non-linear analyses have been done in PERFORM-3D software.